Optimization of sweet potato pectin extraction using hydrochloric acid. Issue 2 (January 2020) - Abang Zaidel, D N; Ismail, N H; Mohd Jusoh, Y M; Hashim, Z; Wan Azelee, N I
Abstract: Pectin has been used widely as thickener, stabilizer and gelling agent. However, the sources of pectin industrially are still limited. This study aims to optimize the extraction of pectin from sweet potato residue using hydrochloric acid. In this study, proximate analysis of the sweet potato residues were performed and the extraction of pectin from sweet potato residues using hydrochloric acid was optimized to maximize its yield using response surface methodology (RSM). Three parameters were manipulated and optimized which were temperature (°C), pH and extraction time (min). The extracted pectin was further analyzed for its degree of esterification (DE) using Fourier Transform Infrared Spectroscopy (FTIR). The sweet potato residue sample obtained moisture content of 79.7±1.7%, ash content of 1.08±0.09% and carbohydrate content of 34.3±2.7%. The optimum condition to extract pectin from sweet potato residues using hydrochloric acid was at extraction temperature 60 °C, pH 1 and extraction time 60 min with 23.48 % pectin yield. The pectin has 57.48% of DE which indicates high methoxyl pectin. The results show that hydrochloric acid can be used as one of the solvents to extract pectin from sweet potato.